ENDOCANNABINOID SYSTEM IN THE PARAVENTRICULAR NUCLEUS OF THE HYPOTHALAMUS MODULATES AUTONOMIC AND CARDIOVASCULAR CHANGES BUT NOT VASOPRESSIN RESPONSE IN A RAT HEMORRHAGIC SHOCK MODEL - Busnardo, Cristiane [UNESP]; Fassini, Aline; Lopes-Azevedo, Silvana; Omena-Giatti, Luana [UNESP]; Goulart, Melissa T.; Antunes-Rodrigues, Jose; Alves, Fernando H. F.; Correa, Fernando M. A.; Crestani, Carlos C. [UNESP] (Wolters Kluwer, 2024)
We evaluated the participation of the endocannabinoid systemin the paraventricular nucleus of the hypothalamus (PVN) on the cardiovascular, autonomic, and plasma vasopressin (AVP) responses evoked by hemorrhagic shock in rats. For this, the PVN was bilaterally treated with either vehicle, the selective cannabinoid receptor type 1 antagonist AM251, the selective fatty acid amide hydrolase amide enzyme inhibitor URB597, the selective monoacylglycerol-lipase enzyme inhibitor JZL184, or the selective transient receptor potential vanilloid type 1 antagonist capsazepine. We evaluated changes on arterial pressure, heart rate, tail skin temperature (ST), and plasma AVP responses induced by bleeding, which started 10 min after PVN treatment. We observed that bilateral microinjection of AM251 into the PVN reduced the hypotension during the hemorrhage and prevented the return of blood pressure to baseline values in the posthemorrhagic period. Inhibition of local 2-arachidonoylglycerol metabolism by PVN treatment with JZL184 induced similar effects in relation to those observed in AM251-treated animals. Inhibition of local anandamidemetabolism via PVNtreatment with URB597 decreased the depressor effect and ST drop induced by the hemorrhagic stimulus. Bilateral microinjection of capsazepine mitigated the fall in blood pressure and ST. None of the PVN treatments altered the increased plasma concentration of AVP and tachycardia induced by hemorrhage. Taken together, present results suggest that endocannabinoid neurotransmission within the PVN plays a prominent role in cardiovascular and autonomic, but not neuroendocrine, responses evoked by hemorrhage.
Keywords: Endocannabinoid; hemorrhagic shock; hypothalamus, cardiovascular; sympathetic activity; vasopressin